L’efficacité visuelle des cartogrammes animés en question. Une piste d’amélioration à travers l’exemple de la ségrégation à Bogotá (1993-2005) - Florent Demoraes; Mégane Bouquet; Boris Mericskay (M@ppemonde)
Cartograms have long been used to highlight the uneven distribution of a phenomenon over a given area. On these maps, the size of spatial units is proportional to their weight (the number of inhabitants, amount of CO2 emitted, etc.). Over the past twenty or so years, the benefits of adding movement to this type of map–mainly to assess changes over time and space–have been discussed. Several methods have been suggested for constructing animated cartograms, and efficient algorithms are now available to distort spatial units. Nevertheless, rendering a second variable on an animated cartogram remains a challenge, generally giving rather poor results. In this article we experiment with a way of improving the effectiveness of such animated cartograms, by conjointly using spatial smoothing. We demonstrate the potential of combining these two mapping techniques in animated mode to visualize changes in socio-residential segregation over time, using the example of Bogotá (Colombia) from 1993 to 2005.